Substantiating social entrepreneurship research: exploring the potential of integrating social capital and networks approaches. (1st January 2014) - Busch, Christian
A relatively recent domain of academic inquiry, social entrepreneurship (SE) has been regarded as a field that transcends the boundaries of academic disciplines (Dacin et al., 2010; Mair and Marti, 2006; Seelos and Mair, 2005). However, while the basic premise to combine financial and social impact has attracted a lot of goodwill from governments, businesses, NGOs, and educational institutions alike, the development of explanatory constructs is still limited (Grimes and Victor, 2009; Hull, 2010). While social entrepreneurs are socially embedded in their local communities and assumed to show the ability to build and maintain networks in order to be able to perform (Alvord et al., 2004; Dacin et al., 2011; Mair and Marti, 2006; Perrini and Vurro, 2006), there has been a lack of theoretical foundation with respect to the surrounding network dynamics. We will argue that integrating social capital/networks approaches into the literature will enhance the academic and practical impact of our approaches, and further advance the field.